Polarographic and spectroscopic studies of the effects of fluoroacetate/fluorocitrate on cells and mitochondria. Issue 2 (2007) - Zinchenko Zinchenko, Valeriy P. Valeriy P.; Goncharov Goncharov, Nikolay V. Nikolay V.; Teplova Teplova, Vera V. Vera V.; Kasymov Kasymov, Vitaliy A. Vitaliy A.; Petrova Petrova, Olga I. Olga I.; Berezhnov Berezhnov, Alexey V. Alexey V.; Senchenkov Senchenkov, Evgeniy V. Evgeniy V.; Mindukshev Mindukshev, Igor V. Igor V.; Jenkins Jenkins, Richard O. Richard O.; Radilov Radilov, Andrey S. Andrey S.
Abstract : Experiments were performed with rat liver mitochondria, Ehrlich ascite tumor cells (EATC) and cardiomyocytes, exposed to fluoroacetate (FA) or fluorocitrate (FC) in vitro . The effects of FA developed at much higher concentrations in comparison with FC and was dependent upon respiratory substrates: with pyruvate, FA induced a slow oxidation of pyridine nucleotides (NAD(P)H) and inhibition of respiration. NAD(P)H oxidation was prevented by incubation of mitochondria with cyclosporin A (CsA), an inhibitor of mitochondrial permeability transition pore. Studies of the NAD(P)H level and calcium response generated in EATC under activation with ATP via the metabotropic P2Y receptor, revealed a loss of NAD(P)H from mitochondria resulting in a shift in the balance of mitochondrial and cytosolic NAD(P)H on exposure to FA. An increase of cytosolic [Ca 2+ ] was observed in the cell lines exposed to FA and is explained by activation of plasma membrane calcium channels; this mechanism could have an impact on amplitude and rate of Ca 2+ waves in cardiomyocytes, and cause the hypersensitivity of platelets reported on earlier. Highlighting the reciprocal relationship between intracellular NAD(P)H and calcium balance, we discuss metabolic pathway modulation in the context of development of an effective therapy for FA poisoning.